2023
DOI: 10.26858/eralingua.v7i1.41955
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perspectives on the Usefulness of ICT -Based Learning by Using Technology Acceptance Model (TAM)

Amrullah Amrullah,
Husnul Lail,
Sofia Rahmi Sumayani
et al.

Abstract: Abstract. In this new era, teaching and learning activities have been associated with the use of Information and Communication Technology (ICT). In the context of English language learning, ICT is a resource and tool for supporting students in their learning process. With the use of different English learning activities, ICT offers students a range of sources to obtain authentic content and improve their language abilities. This research aims to analyze the English as a Foreign Language (EFL) students’ perspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Additionally, previous research, such as that by Alkaromah et al (2020) and Ningsih et al (2022) on high school students' perceptions of ICT use in ELT, and studies by Amrullah et al (2023), Arif (2019), Basri and Paramma (2019), and Wiyaka et al (2018) on university students, indicates mixed perceptions toward ICT integration in ELT. However, insights from these studies may not fully translate to the vocational school context due to differing educational priorities and environments (Berk, 2022).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Additionally, previous research, such as that by Alkaromah et al (2020) and Ningsih et al (2022) on high school students' perceptions of ICT use in ELT, and studies by Amrullah et al (2023), Arif (2019), Basri and Paramma (2019), and Wiyaka et al (2018) on university students, indicates mixed perceptions toward ICT integration in ELT. However, insights from these studies may not fully translate to the vocational school context due to differing educational priorities and environments (Berk, 2022).…”
Section: Introductionmentioning
confidence: 90%
“…It was found that students have positive responses to the integration of ICT in any form of it in English language learning because it makes learning Journal on English as a Foreign Language,14(1), 285-315 p-ISSN 2088285-315 p-ISSN -1657e-ISSN 2502-6615 easier and motivates them to learn more. In addition, studies were conducted at the university level by Amrullah et al (2023), Arif (2019), Basri and Paramma (2019), and Wiyaka et al (2018) clarified several perspectives on ICT in general. These views range from positive to negative.…”
Section: Introductionmentioning
confidence: 99%
“…The emerging popularity of web technologies and their applications has created new opportunities for higher education institutions (Handayani & Sudiana, 2015;Amrullah, 2023;Susanto et al, 2022). Management of higher education is currently unable to separate from the use of information technology (Meilani et al, 2020).…”
Section: Introductionmentioning
confidence: 99%